Engineering human PrimPol into an efficient RNA-dependent-DNA primase/polymerase - Agudo, Rubén (Nucleic Acids Res, 2017)
We have developed a straightforward fluorometric assay to measure primase-polymerase activity of human PrimPol (HsPrimPol). The sensitivity of this procedure uncovered a novel RNA-dependent DNA priming-polymerization activity (RdDP) of this enzyme. In an attempt to enhance HsPrimPol RdDP activity, we constructed a smart mutant library guided by prior sequence-function analysis, and tested this library in an adapted screening platform of our fluorometric assay. After screening less than 500 variants, we found a specific HsPrimPol mutant, Y89R, which displays 10-fold higher RdDP activity than the wild-type enzyme. The improvement of RdDP activity in the Y89R variant was due mainly to an increased in the stabilization of the preternary complex (protein:template:incoming nucleotide), a specific step preceding dimer formation. Finally, in support of the biotechnological potential of PrimPol as a DNA primer maker during reverse transcription, mutant Y89R HsPrimPol rendered up to 17-fold more DNA than with random hexamer primers.